On fixed point results for a class of generalized mean nonexpansive mappings - Mebawondu, A. A.; Izuchukwu, C.; Oyewole, K. O.; Mewomo, O. T. (Methods of Functional Analysis and Topology, 2020)
In this paper, we introduce a new class of generalized mean nonexpansive mappings and propose an iterative algorithm for approximating the fixed points of this class of mappings in the frame work of uniformly convex Banach spaces. We establish some fixed point results for this class of mappings and prove the convergence of the propose iterative algorithm. Finally, numerical experiment is presented to demonstrate the efficiency of our algorithm in comparison with other existing algorithms in literature. Вводиться новий клас узагальнених нерозтягуючих у середньому відображень, для яких пропонується ітераційний алгоритм наближеного знаходження нерухомих точок в контексті рівномірно опуклих банахових просторів. Для цього класу відображень доведені теореми про нерухому точку, а також збіжність зазначеного алгоритму. Шляхом чисельного експерименту наш алгоритм порівнюється з відомими.